2019
DOI: 10.3892/ol.2019.10716
|View full text |Cite
|
Sign up to set email alerts
|

Valosin‑containing protein promotes metastasis of osteosarcoma through autophagy induction and anoikis inhibition via the ERK/NF‑κβ/beclin‑1 signaling pathway

Abstract: Valosin-containing protein (VCP) promotes the development of metastasis in osteosarcoma (OS) via the PI3K/Akt signaling pathway. However, inhibition of the PI3K/Akt pathway does not completely reverse VCP-mediated invasion and migration of OS, suggesting that VCP-mediated OS invasion and migration involves additional mechanisms. In the present study, a positive correlation between the expression of VCP and cell autophagy was observed among OS tissues. Inhibiting VCP may decrease the survival of malignant cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Thus, approaches targeting the VCP/miR-129-5p signaling pathway might represent a therapeutic strategy for osteosarcoma management [ 93 ]. Moreover, the authors of a recent study modulated VCP/p97 expression and observed a connection with autophagy induction, anoikis resistance and osteosarcoma cell metastasis [ 94 ]. An interesting study assessing Saos-2 osteosarcoma cells highlighted a novel regulatory mechanism mediated by the serum amyloid p (SAP) protein, an apoptotic inducer that binds to VCP/p97, precluding it from exerting an anti-apoptotic effect [ 95 ].…”
Section: Vcp/p97 Expression and Function In Cancermentioning
confidence: 99%
“…Thus, approaches targeting the VCP/miR-129-5p signaling pathway might represent a therapeutic strategy for osteosarcoma management [ 93 ]. Moreover, the authors of a recent study modulated VCP/p97 expression and observed a connection with autophagy induction, anoikis resistance and osteosarcoma cell metastasis [ 94 ]. An interesting study assessing Saos-2 osteosarcoma cells highlighted a novel regulatory mechanism mediated by the serum amyloid p (SAP) protein, an apoptotic inducer that binds to VCP/p97, precluding it from exerting an anti-apoptotic effect [ 95 ].…”
Section: Vcp/p97 Expression and Function In Cancermentioning
confidence: 99%
“…Inhibition of VCP expression may suppress OS metastasis by modulating the PI3K/NF-κβ signaling pathway (19). However, our previous study revealed that inhibition of the PI3K/NF-κβ pathway does not completely reverse VCP-mediated invasion and migration of OS (Long et al, unpublished The further study found that VCP could induces autophagy and inhibits anoikis to promote osteosarcoma metastasis [30]. But the level of autophagy has no effect on the invasion and metastasis ability of OS cells, which suggests that other mechanisms of VCP-mediated OS invasion and migration may be involved.…”
Section: Discussionmentioning
confidence: 92%
“…However, although stromal cells produce over 90% of the ECM mass [30], it was demonstrated that proteins of the ECM are highly expressed in pancreatic cancer cells [31] and elevated levels of ECM proteins derived from tumor cells of pancreatic cancer, but not those produced exclusively by stromal cells, tend to correlate with poor patient survival in pancreatic cancer [30]. The identified proteins are involved in cell migration (Collagen alpha-2(I) chain) [32], effected cancer cell motility (Actin) [33], promotion of metastasis (Valosin-containing protein) [34], cancer cell viability, angiogenesis (Collagen alpha-3(VI) chain) [35] and tumor progression (Collagen alpha-2(I) chain) [36].…”
Section: Discussionmentioning
confidence: 99%